Nanotechnology for the delivery of therapeutic nucleic acids - Peer, Dan, 1972- (Singapore : Pan Stanford Publishing, 2013)
Nucleic acid (NA) therapeutics has been extensively studied both in the academia and in the pharmaceutical industry and is still considered the promise for new therapeutic modalities, especially in personalized medicine. The only hurdle that limits the translation of NA therapeutics from an academic idea to the new therapeutic modality is the lack of efficient and safe delivery strategies. Nanotechnology for the Delivery of Therapeutic Nucleic Acids , written by world experts in the field of nanotechnology for NA delivery, the contributing authors bring together the state of the art in delivery strategies with strong emphasis on aspects that are of essence to the pharmaceutical industry, such as stability, general toxicity, immune-toxicity, pharmacokinetics, efficacy, and validation of new drug targets using unique approaches based on exquisite nanotechnology strategies.
Lipoplexes and polyplexes : from gene delivery to gene expression / Gerardo Byk, Mirit Cohen-Ohana, and Fiana Mirkin -- 2. Cationic polymers for the delivery of therapeutic nucleotides / Wahid Khan, Saravanan Muthupandian, and Abraham J. Domb -- 3. Membrane/core nanoparticles for delivery of therapeutic nucleic acid / Younjee Chung and Leaf Huang -- 4. Delivery of single siRNA molecules / Caroline Palm-Apergi and Steven F. Dowdy -- 5. Cell-specific aptamer-functionalized RNAi : a new prospect for targeted siRNA delivery / Jiehua Zhou and John J. Rossi -- 6. Bioresponsive nanoparticles for the intracellular delivery of RNAi therapeutics / Kenneth Alan Howard -- 7. Lipid-like delivery materials for efficient siRNA delivery / James Dahlman, Robert Langer, and Michael Goldberg -- 8. Manipulation of leukocytes using therapeutic RNAi delivered by targeted and stabilized nanoparticles / Dan Peer -- 9. Lowering the siRNA delivery barrier : alginate scaffolds and immune stimulation / Jana McCaskill, Sherry Wu, Norliana Khairuddin, and Nigel A.J. McMillan.
pharmacy bookfair2015
Keywords: Drug delivery systems; Nucleic acids; Nanotechnology